Nile BDC hard seat—the 3rd International Forum on Water and Food - Douthwaite, Boru (International Livestock Research Institute, 2011)
In this 'hard seat' interview on 6 May 2011, Matthew McCartney (IWMI) interviewed Boru Douthwaite (CPWF) about plans for the 3rd International Forum on Water and Food to be held in South Africa in November 2011—http://www.waterandfood.org/ifwf3/. The interview was part of the Nile Basin Development Challenge (http://nilebdc.org) 'science and reflection' workshop in Addis Ababa in May 2011.